Polyarteritis Nodosa Presenting with Ischemic Stroke: A Case Report - Samaher Almousa; Ritta Muhamad; Farah Salameh; Abdallah Alahmad; Bana Kasem; Hala Wannous (Disease and Diagnosis)
Polyarteritis nodosa (PAN) is a rare inflammatory necrotizing vasculitis with variable clinical manifestations and unusual presentations. Therefore, delays in diagnosis are common. The most common features are polyneuropathy, gastrointestinal, and constitutional symptoms. Central nervous system (CNS) involvement is rare in this disease, manifesting as encephalopathy, headache, seizures, and stroke. However, stroke can be ischemic or hemorrhagic, and it is extremely rare as an initial manifestation of PAN. Here, we present a 67-year-old male patient who presented with an initial stroke. He was diagnosed with PAN when he developed severe multi-system complications leading to death. We aim to increase awareness about this disabling complication of PAN and highlight the importance of considering vasculitis, especially PAN, in the differential diagnosis of ischemic stroke. Early diagnosis and timely treatment can improve clinical outcomes and decrease mortality rates.